The importance of quality and consistent target volume definition in the treatment of locally advanced non-small cell lung cancer - Badiyan, Shahed N.; Roach, Michael C.; Vlacich, Gregory; Robinson, Cliff G.; Bradley, Jeffrey D. (Therapeutic Radiology and Oncology, 2018)
The Advisory Committee on Radiation Oncology Practice (ACROP) of the European Society for Radiotherapy and Oncology (ESTRO) has developed a number of high quality radiation oncology practice guidelines since its inception in 2012 (1-6). Recently, the committee published an excellent set of guidelines focused on target volume definition in the treatment of locally advanced non-small cell lung cancer (NSCLC), an area in which there is considerable variability in practice (7). This article aims to comment on data behind the key elements of this guideline and the future direction of radiation therapy (RT) treatment planning for locally-advanced NSCLC.